Managing the Open Access publication process: Bentham Science and Research Square (Pubmet, 2022)
Come learn about Bentham Science Open for journals and e-books and get insights about Managing the Open Access Publication Process. This presentation will focus on helping you understand the publication process, from how to submit a scientific paper through to how to manage your interactions with editors and reviewers to maximize your chances of a successful high-impact outcome for your research.As a result of this course learners will understand:▸ how to effectively submit scientific papers;▸ write highly effective cover letters;▸ select effective and suitable reviewers;▸ ensure your work has the highest possible chance of getting published in your target journal;▸ how to effectively communicate with editors and what they expect from authors and reviewers,and;▸ maximize the impact of your research after publication.Course ContentThe stages of publication:▸ what editors expect from submissions▸ navigating formatting requirements▸ an amazing cover letter – details and selling your work▸ initial review and how to survive▸ ensure your papers gets out for peer-review▸ dealing with peer-review comments, especially those you disagree with▸ managing your editor▸ revisions: how to do the most effective job while making the least number of changes▸ surviving rejection▸ how to make complaints if you feel unfairly treated